Microenterprise Sustainability in Islamic Microfinance - Mohamad Bastomi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study fills a gap in prior research by jointly examining Islamic financial literacy, intellectual capital, and working capital in Baznas Microfinance Desa and by testing financial performance as the mechanism through which these factors sustain microenterprises. Research Objectives: This study analyzes the determinants of microenterprise sustainability among Baznas Microfinance Desa partners in East Java, Indonesia. Research Methods: Using a quantitative explanatory design, data were collected from 285 respondents through five-point Likert-scale questionnaires and analyzed with PLS-SEM. Empirical Results: Islamic financial literacy, intellectual capital, and working capital significantly enhance financial performance and microenterprise sustainability. Working capital shows the strongest contribution, while financial performance has the largest direct effect on sustainability and significantly mediates the relationships between the three determinants and sustainability. Implications: Islamic microfinance programs should prioritize working-capital management while strengthening Islamic financial literacy and capability-oriented mentoring to build intellectual capital, as these factors improve financial performance and, in turn, sustain microenterprises. JEL Classification: D14, G21, G32, L25 How to Cite:Bastomi, M. (2026). Microenterprise Sustainability in Islamic Microfinance. Signifikan: Jurnal Ilmu Ekonomi, 15(2), 615-626. https://doi.org/10.15408/sjie.v15i2.50242.